A dive into the marketing trends of 2024: insights to unlocking potential - Vladimir Zhechev (Business & Management Compass, 2024)
Marketing is witnessing unparalleled growth of solutions and innovations that can supercharge those market players ready to embrace the capabilities of GenAI, ML, LLMs, AR/VR, among others. Moreover, displaying brand engagement and sustainability sets new standards in marketing tactics. Various leading marketing agencies have dedicated great deal of research and analytical effort to produce reports including noteworthy marketing trends that can aid CMOs in dealing with the dynamics of the landscape. Whilst most of these reports revolve around technologies and customer experience, few of them give strategic orientation to companies of different size and industry as to how to exploit the opportunities of the new (marketing) reality. In view of this, the aim of this paper is to synthesize, contrast and evaluate some of the newest marketing reports by the industry’s leading companies. This review identifies the commonplace trends; major industries and contrasts them according to content and orientation. One limitation of the paper is that it does not attempt to cover all existing reports in marketing but the ones published by some of the most reputable sources and thus – to combine viewpoints and draw conclusions for businesses. This article provides context and agenda for entrepreneurs and marketing experts pertaining to their future marketing efforts. The originality of this paper resides with the fact that it examines the most contemporary trends in marketing as seen by world-renowned consults, strategists, CMOs and other decision-makers.